Feasibility/Acceptability of an Acceptance-Based Therapy Intervention for Diverse Adolescent Cisgender Girls With Overweight/Obesity. (7th June 2021) - Cardel, Michelle; Lee, Alexandra; Chi, Xiaofei; Newsome, Faith; Miller, Darci; Bernier, Angelina; Thompson, Lindsay; Gurka, Matthew; Janicke, David; Butryn, Meghan
Abstract: Objectives: This study assessed the feasibility and acceptability of an ABT healthy lifestyle intervention among diverse adolescent cisgender girls with overweight/obesity (OW/OB). Methods: Adolescent cisgender girls ages 14 to 19 with a BMI ≥ 85 th percentile-for-sex-and-age were recruited for participation in a single-arm feasibility study. The primary outcomes were recruitment and retention while the secondary outcome was change in BMI Z-score over the 6-month intervention. Exploratory outcomes included obesity-related factors, health-related behaviors, and psychological factors. Results: Recruitment goals were achieved; thirteen adolescents (>60% racial/ethnic minorities) participated in the intervention, and eleven completed the intervention (85% retention). In completers ( n  = 11), a mean decrease in BMI Z-score of −0.15 (SD = 0.34, Cohen's d = −0.44) was observed. Improvements were also noted for change in percentage of 95 th percentile ( d = −0.35), % body fat ( d = −0.35), quality of life ( d  = 0.71), psychological flexibility ( d = −0.86), and depression ( d = −0.86). Conclusions: These preliminary findings suggest an ABT healthy lifestyle intervention tailored for adolescent cisgender girls with OW/OB may be an acceptable treatment that could lead to improvements in BMI Z-score, obesity-related measures, and psychological outcomes. Funding Sources: This work is supported by the National Center for Advancing Translational Sciences of the National Institutes of Health (NIH; UL1TR001427) and WellCare Health Plans, Inc. Dr. Cardel is also supported by the National Institutes of Health National Heart, Lung, and Blood Institute (K01HL141535 and R25HL126146).